Draft Genome Sequences of Elizabethkingia anophelis Strains R26(T) and Ag1 from the Midgut of the Malaria Mosquito Anopheles gambiae - Kukutla, Phanidhar (American Society for Microbiology, 2013)
Elizabethkingia anophelis is a species in the family Flavobacteriaceae. It is a dominant resident in the mosquito gut and also a human pathogen. We present the draft genome sequences of two strains of E. anophelis, R26(T) and Ag1, which were isolated from the midgut of the malaria mosquito Anopheles gambiae.